Does digitalization increase labor market efficiency? Job search and effort on the job with asymmetric information and firm learning - Karin Mayr-Dorn (Johannes Kepler University of Linz, Department of Economics, 2019)
This paper analyses the effect of firm learning on labor market efficiency in a frictional labor market with asymmetric information. I consider a model with random matching and wage bargaining a la Pissarides (1985, 2000) where worker ability is unknown to firms at the hiring stage. Firm learning increases relative expected earnings in high-ability jobs and, thereby, enhances imitation incentives of low-ability workers. The net effect on aggregate expected match surplus and unemployment is indeterminate a priori. Numerical results show that firm learning does not increase labor market efficiency.
Keywords: D82; D83; J64; 330; job search; on-the-job effort; asymmetric information; learning